Influence of Reclaimed Asphaltic Pavement (RAP) on Cold Mix Asphalt performance - Rusli, Nurul Billahizzati; Basri, Nur Khairiyah; Wan Azahar, Wan Nur Aifa; Md. Husain, Nadiah; Wan Hassan, Wan Nur Firdaus; Ramli, Ahmad Bukhari; Che Deraman, Siti Noratikah; Md Kassim, Tahara Ramadzan (Springer, 2025)
Cold mix asphalt (CMA) technology is commonly used in maintenance work like repairing potholes. It is convenient to use in road maintenance because it does not require any heating process that will ease the transporting and storing operation. The performance of incorporating reclaimed asphalt pavement (RAP) in CMA was explored in this research. Six CMA samples were prepared for this inves-tigation including 0, 20, 40, 60 80 and 100% RAP to determine the most optimum RAP content in replacing the virgin aggregate. Two stages of experiments were conducted: LAAV tests as well as Marshall Stability Test. The results show that the stability for patching pothole mix was greater than 6.0 kN where all samples with 6.1% OBC except 0% RAP and 100% RAP meet Road Engineering Asso-ciation Malaysia (REAM) criteria. Furthermore, all samples except 40% RAP did not exceed REAM requirements. However, all OBC samples except 20% RAP and 6.1% OBC meet REAM specifications. All flow rates were 2–5 mm. The balanced flow value ensures the mix is flexible enough to avoid cracking and rigid enough to survive rutting and deformation. Stability, flow, and stiffness tests show that adding 40% RAP to CMA increases stability and stiffness. The stability, flow, and stiffness of 40% RAP and 60% aggregate were much better than the control sample. The sample had the maximum stiffness at 3028.571 N/mm and 4404.854 N/mm for OBC 6.1% and 6.2%. Stability, flow, and stiffness fulfil REAM pothole mixed pathing guidelines, ensuring the reliability and durability of the design. Therefore, it can be concluded that 40% RAP is the best combination aggregate for cold mix asphalt pothole repair.